PENGGELOLAAN KOTAK REVIEW/ULASAN PADA SISTEM PENJUALAN PADA TOKO ONLINE - Suriyanto, Adhi Dharma (Jurnal Komunikasi, 2016)
Earth's population growth impact on the sharpening competition to win to survive. Man with his wits to develop science one of which is the development of information technology and computers became a prelude to the creation of an online store. A modern model of selling goods that promises comfort, security and progress in the attempt. The management needs to be an important thing to win the competition. Box reviews a concern in this paper, how it became an important. keywords: Box reviews, online store